1990
DOI: 10.3758/bf03205326
|View full text |Cite
|
Sign up to set email alerts
|

The effects of taste extinction on ingestional potentiation in weanling rats

Abstract: Four experiments investigated taste potentiation in weanling rats. In Experiment 1, the animals that drank a conditioning compound of denatonium and saccharin consumed significantly less on the test than controls that drank only saccharin during conditioning. This enhanced saccharin aversion was decremented by postconditioning extinction to denatonium in Experiment 2, and no generalization of saccharin aversions to the denatonium was observed in Experiment 3. Extinction of either saccharin or denatonium aversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…However, in addition to groups of rats that dranksaccharin during conditioning, there were also groups that drank a compound solution consisting of saccharin and denatonium saccharide. These tastes were used because previous work indicates that saccharin reliably overshadows denatonium aversions (Davis, Best, & Grover, 1988) and that aversions between these two tastes do not readily generalize to one another or punish the animals' drinking of either (Davis et al, 1990). Denatonium tests were then administered either 1 day or 21 days after conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…However, in addition to groups of rats that dranksaccharin during conditioning, there were also groups that drank a compound solution consisting of saccharin and denatonium saccharide. These tastes were used because previous work indicates that saccharin reliably overshadows denatonium aversions (Davis, Best, & Grover, 1988) and that aversions between these two tastes do not readily generalize to one another or punish the animals' drinking of either (Davis et al, 1990). Denatonium tests were then administered either 1 day or 21 days after conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…However, Schweitzer and Green (1982) reported an opposite result in a similar preparation, as did Marlin (1982, Experiments 1 and 2) in a study of contextual extinction (see also Balaz, Capra, Hartl, & Miller, 1981;Grahame, Hallam, Geier, & Miller, 1990). The opposite results were also found in appetitive conditioning with rats (Holland & Ross, 1981), in keypeck conditioning with pigeons (Rescorla, 1983), in keylightcontext compound conditioning with pigeons (Rescorla, 1984), in nictitating membrane conditioning with rabbits (Gibbs, Kehoe, & Gormezano, 1991), in taste aversion with rats (Davis, Best, & Grover, 1988;Davis, Best, Grover, Bailey, Freeman, & Mayleben, 1990;Durlach & Rescorla, 1980;Rescorla & Cunningham, 1978), in taste-odor compound conditioning with rats (Miller, McCoy, Kelly, & Bardo, 1986), in taste-context compound conditioning with rats (Best, Batson, Meachum, Brown, & Ringer, 1985), and in taste-color compound conditioning with pigeons (Thiele & Frieman, 1994).…”
mentioning
confidence: 87%
“…Rescorla and Durlach (1981) demonstrated that repeated presentation of a stimulus compound promoted within-compound learning. Among the taste or taste-odor aversion studies described above, Kalat and Rozin (1972), Lett (1984), and Revusky et al (1977) poisoned the compound once, but Best et al (1985), Davis et al (1990), Miller et al (1986), and Speers et al (1980) poisoned the compound more than once. The direction of the results of the former three accorded with the retrospective view but that of the latter four did not.…”
mentioning
confidence: 99%
“…In rats, it has been found that taste potentiates the aversive reaction to an odor (e.g., Droungas & LoLordo, 1991;Durlach & Rescorla, 1980;Kiefer, Rusiniak, & Garcia, 1982;Lett, 1984;Miller, McCoy, Kelly, & Bardo, 1986;Palmerino, Rusiniak, & Garcia, 1980;Rusiniak, Hankins, Garcia, & Brett, 1979;Westbrook, Homewood, Horn, & Clarke, 1983), to visual properties of conditioned stimuli (Galef & Osborne, 1978), to auditory properties of conditioned stimuli (Ellins, Cramer, & Whitmore, 1985;Ellins & von Kluge, 1987), to the conditioning environment (Best, Batson, Meachum, Brown, & Ringer, 1985;Best & Meachum, 1986;Miller et al, 1986), and to a second taste (Davis, Best, & Grover, 1988;Davis et al, 1990;Kucharski & Spear, 1985). In birds, it has been found that taste potentiates the aversive reaction to colored water (Franchina, Wright, Smith, Penn, & Soeken, 1993;Jackson & Fritsche, 1989;Lett, 1980Lett, , 1984 and to colored food (Brett, Hankins, & Garcia, 1976;Martin & Lett, 1985).…”
mentioning
confidence: 98%
“…In the taste-potentiated odor-aversion paradigm, several authors have found that postconditioning extinction of the taste aversion attenuated associated odor aversions (Durlach & Rescorla, 1980;Miller et al, 1986;Westbrook et al, 1983). Likewise, several authors have found that when one taste is used to potentiate the aversive reactions to a second taste, postconditioning extinction of one taste aversion attenuates the potentiated aversion to the second taste (Davis et al, 1988;Davis et al, 1990;Kucharski & Spear, 1985). And in a paradigm in which a taste was used to potentiate environmental aversions, it has been found that postconditioning extinction of the taste aversion attenuated potentiated environmental aversions (Best et al, 1985).…”
mentioning
confidence: 99%